ACANTHOCEPHALANS OF FISH FROM THE NORTHWESTERN JAPAN SEA - Z. I. Motora (Известия ТИНРО)
Parasitic fauna of marine fishes in the northwestern Japan Sea is studied since 1929, when its investigation was started by E.M. Lyayman. The results concerning acanthocephalan worms were presented in several publications, including the papers about parasitic fauna of certain fish families or in certain areas of the Sea and the first description of a new species as Echinorhynchus theragrae from walleye pollock. This information is catalogued by E.M. Didenko and G.G. Shevchenko (1999), who presented a list of 25 Acanthocephala species from marine and anadromous fishes, including 4 unidentified ones. The study is continuing with expanding of the species lists for the region and for the hosts. New summary of all available data on acanthocephalan worms is presented, with quantitative data on their contamination of marine, anadromous and semi-anadromous fishes in the northwestern Japan Sea. In total, 2507 fish specimens belonged to 70 species, 53 genera, 25 families, and 13 orders were investigated in the period since 1997 to 2018 and 38 species of acanthocephalan worms were found belonged to 13 genera, 7 families, 4 orders, and 2 classes, mostly to the geni Echinorhynchus (8 species) and Corynosoma (5 species). Among these 38 species, 13 ones are new for the northwestern Japan Sea (Acanthogyrus (A.) lizae, Neoechinorhynchus agilis, Echinorhynchus lotellae, E. yamagutii, Pseudorhadinorhynchus samegaiensis, Metacanthocephaloides zebrini, Metacanthocephalus pleuronichthydis, Rhadinorhynchus cololabis, Andracantha mergi juv., Bolbosoma nipponicum juv., Bolbosoma sp. juv., Corynosoma osmeri juv., C. validum juv.) and 3 are noted for the first time in marine fish of the Japan Sea (E. yamagutii, A. mergi, C. validum). Intermediate hosts are determined and spatial distribution is described for each species. The most of acanthocephalan species are hosted by the fishes of families Pleuronectidae, Salmonidae and Gadidae (15, 14 and 13 species, respectively); on opposite, the fishes of family Trichodontidae are infested by 2 species only. New hosts are determined for 19 species of acanthocephalans. Mass contamination of fish by E. gadi, E. cotti, C. strumosum juv., and B. caenoforme juv. is detected.